2017
DOI: 10.1508/cytologia.82.75
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Karyotype and Idiogram of Bengal Monitor Lizard, <i>Varanus bengalensis</i> (Squamata, Varanidae)

Abstract: The standardized karyotype and idiogram of the Bengal monitor lizard (Varanus bengalensis) from the Kalasin Province of Thailand were studied. Blood samples were taken from male and female lizards. The standard T-lymphocyte cell was cultured at 26 C for 96 h. The mitotic chromosomes were harvested by colchicine-hypotonic-fixation-air drying technique. Conventional staining, Ag-NOR banding and C-banding techniques were applied to stain the chromosome with 20% Giemsa s solution. The results showed that the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The first evidence of sex chromosomes came from the study of the genus Varanus with the description of a ZZ/ZW sex minichromosomes in four species [238,239]. Later, this ZW system was discovered in other species [240][241][242]. Lastly, chromosome painting probes of Varanus komodoensis allowed the discovery of ZZ/ZW sex minichromosomes in six other species and demonstrated that the Z chromosome was conserved in 12 species covering all the phylogenetic diversity of the genus [243].…”
Section: Anguimorphamentioning
confidence: 99%
“…The first evidence of sex chromosomes came from the study of the genus Varanus with the description of a ZZ/ZW sex minichromosomes in four species [238,239]. Later, this ZW system was discovered in other species [240][241][242]. Lastly, chromosome painting probes of Varanus komodoensis allowed the discovery of ZZ/ZW sex minichromosomes in six other species and demonstrated that the Z chromosome was conserved in 12 species covering all the phylogenetic diversity of the genus [243].…”
Section: Anguimorphamentioning
confidence: 99%
“…Monitors are also the cytogenetically most studied group of the anguimorphan clade. The karyotype has been so far described in 30 species [ 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. All species of monitors show karyotypes with the 2n = 40 chromosomes (16 macro- and 24 microchromosomes) and similar morphology of chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…For the C-banding technique of the present experiment, we treat the chromosomes with 0.2 N HCl for 15 min at room temperature and 0.05 N Ba(OH) 2 for 15 min at 37 C to break the histone protein throughout the euchromatin and loosen the heterochromatin, and stain them with 20% Giemsa solution for 30 min. Our result showed the appearance of constitutive heterochromatin in various regions on each chromosome that included centromeric, subcentromeric, some interstitial and some telomeric regions (Patawang et al 2017). The DAPI staining was made by the standard method of FISH technique; chromosomes were digested by 10 mM HCl and pepsin, from porcine gastric mucosa, for five minutes at 37 C and then stabilized with a postfixsolution (2% paraformaldehyde, 1 PBS and 1 M MgCl 2 solution) for 10 min at room temperature and stained with antifade-4′,6-diamidino-2-phenylindole solution in a dark chamber.…”
mentioning
confidence: 58%